2019
DOI: 10.1055/s-0039-1690688
|View full text |Cite
|
Sign up to set email alerts
|

Isothiazoles in the Design and Synthesis of Biologically Active Substances and Ligands for Metal Complexes

Abstract: The chemistry of isothiazoles is being intensively developed, which is evidenced by the wide range of selective transformations involving the isothiazole heterocycle and the high biological activity of its derivatives that can be used as effective new drugs and plant protection chemicals. Some representatives of isothiazoles have proven to be synergists of bioactive substances, which opens the way to lower the doses of drugs used and is especially important in cancer chemotherapy. In the framework of the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 114 publications
(119 reference statements)
0
19
0
1
Order By: Relevance
“…Compounds with the five-membered isoxazole, isothiazole and 1,3,4-thiadiazole heterocycles possess high potential for biological activity and are privileged scaffolds for the development of pharmaceutical agents (Das & Chanda, 2021;Kletskov et al, 2020;Khalilullah et al, 2014;Yadigarov et al, 2009;Safavora et al, 2019;Zubkov et al, 2014). In particular, isoxazoles are able to enhance the action of 'first-line' antitumor substances, which makes it possible to reduce their therapeutic doses and thus reduce toxic side effects (Khalilov et al, 2021;Kulchitsky et al, 2012;Naghiyev et al, 2020).…”
Section: Chemical Contextmentioning
confidence: 99%
“…Compounds with the five-membered isoxazole, isothiazole and 1,3,4-thiadiazole heterocycles possess high potential for biological activity and are privileged scaffolds for the development of pharmaceutical agents (Das & Chanda, 2021;Kletskov et al, 2020;Khalilullah et al, 2014;Yadigarov et al, 2009;Safavora et al, 2019;Zubkov et al, 2014). In particular, isoxazoles are able to enhance the action of 'first-line' antitumor substances, which makes it possible to reduce their therapeutic doses and thus reduce toxic side effects (Khalilov et al, 2021;Kulchitsky et al, 2012;Naghiyev et al, 2020).…”
Section: Chemical Contextmentioning
confidence: 99%
“…1,2-Azoles are five-membered heterocycles containing at least one nitrogen atom and privileged structures widely found in pharmaceuticals 1 7 , pesticides 8 , and chiral catalysts 9 or ligands 10 , 11 (Fig. 1a ).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it was found that isothiazole derivatives are promising candidates for synergist's role. Isothiazole (1,2-thiazole) nucleus has high potential of biological activity and is structural part of a wide range of synthetic bioactive substances [5].…”
Section: Introductionmentioning
confidence: 99%